2016
DOI: 10.1101/093500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The triple-flash illusion reveals a driving role of alpha-band reverberations in visual perception

Abstract: The modulatory role of spontaneous brain oscillations on perception of threshold-level stimuli is well established. Here, we provide evidence that alpha-band (7-14 Hz) oscillations not only modulate but also can drive perception. We used the "triple-flash" illusion: Occasional perception of three flashes when only two spatially-coincident veridical ones are presented, separated by ~100 ms. The illusion was proposed to result from superposition of two hypothetical oscillatory impulse response functions (IRF) ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…100 ms; Bowen, ). Consistent with this idea, the optimal stimulus onset asynchrony for this illusion has been found to correlate with individual peak alpha frequency in parietal, but not occipital cortex (Gulbinaite et al ., ). This finding suggests that alpha oscillations can induce experiences of visual stimuli that have not been presented, further supporting the positive association between alpha and visual perception.…”
Section: The Characters Of Alphamentioning
confidence: 97%
“…100 ms; Bowen, ). Consistent with this idea, the optimal stimulus onset asynchrony for this illusion has been found to correlate with individual peak alpha frequency in parietal, but not occipital cortex (Gulbinaite et al ., ). This finding suggests that alpha oscillations can induce experiences of visual stimuli that have not been presented, further supporting the positive association between alpha and visual perception.…”
Section: The Characters Of Alphamentioning
confidence: 97%
“…Recent studies have suggested that pre-stimulus alpha activity may reflect the criterion used to commit a specific response and may hence reflect a perceptual or decisional bias (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Rohe, Ehlis, & Noppeney, 2019). Along such a role in perceptual decision making, alpha activity was shown to correlate with subjective awareness (Benwell, et al, 2017;Lange, Oostenveld, & Fries, 2013;Gulbinaite, İlhan, & VanRullen, 2017) and decision confidence (Samaha, Iemi, & Postle, 2017;Wöstmann, Waschke, & Obleser, 2018). Still, it remains unclear whether pre-stimulus activity indeed reflects an individual's intrinsic bias, or reflects processes that facilitate veridical sensory encoding, as previous work did not unambiguously quantify the relation of spontaneous brain activity to idiosyncratic and temporary biases.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Milton and Pleydell‐Pearce (Milton & Pleydell‐Pearce, ) provided renewed evidence accounting for the role of alpha phase in perception of visual synchrony (see also VanRullen & Koch, ). Another piece of evidence which relates spontaneous oscillations in the alpha band and temporal perception comes from studies which correlate the peak frequency in the alpha band with visual temporal resolution (Gulbinaite, İlhan, & VanRullen, ; Samaha & Postle, ). Specifically, Samaha and Postle () showed that individual alpha frequency (IAF) correlates with two‐flash fusion thresholds (i.e., perception of two flashes as one when they are presented within the individual alpha cycle).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gulbinaite et al. () demostrated that individual alpha phase and power correlate with the perception of the triple flash illusion (perception of a third flash when only two flashes are presented). Collectively, these results suggest that the speed of alpha oscillations can reflect the temporal resolution of visual perception (Gulbinaite et al., ; Milton & Pleydell‐Pearce, ; Samaha & Postle, ; Varela et al., ).…”
Section: Introductionmentioning
confidence: 99%